Blood pressure among children and adolescents with normal weight but large waist circumference in Shandong, China - Ying-xiu, Zhang; Da-yong, Sun; Jing-yang, Zhou; Jin-shan, Zhao; Zun-hua, Chu (European journal of pediatrics, 2014)
The present study examined the blood pressure (BP) characteristics of normal weight children and adolescents with a large waist circumference (WC) in a large population in Shandong, China. A total of 38,826 students (19,460 boys and 19,366 girls) aged 7–17 years participated in this study. Height, weight, WC, and BP of all subjects were measured. Normal weight was defined by the international cutoffs of body mass index; central obesity was defined as WC ≥90th percentile; relatively high BP status was defined as systolic blood pressure (SBP) and/or diastolic blood pressure (DBP) ≥95th percentile for age and gender. And 5.06 and 8.19 % of the normal weight boys and girls had central obesity. The Z-scores of SBP, DBP and the prevalence of relatively high BP for both boys and girls were all significantly higher in the normal weight with central obesity groups than in the normal weight with normal WC groups. Conclusion : These observations highlight that normal weight children and adolescents with central obesity might have an increased risk of elevated BP.